Comparison of Arterial Line Patency in Heparinized Normal Saline with Normal Saline Flushing Among Critically ill Patients: A Literature Review - Aan Nuraeni; Muhammad Iqbal; Roulita Roulita; Nurlaeci Nurlaeci; Ristina Mirwanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Hemodynamic monitoring in critically ill patients is often invasive, using an arterial line. The monitoring accuracy is highly dependent on the patency of the arterial line, which is often compromised by artery blockages. So far, heparin in normal saline is believed to prevent these complications compared to normal saline alone. This study aimed to compare the effectiveness of normal saline flushing with heparin with normal saline use on arterial line patency. The method of the study was a review. Keywords were compiled using words such as critical care unit, heparinized saline, normal saline, and arterial line patency with boolean operators. Searched extensively through PubMed, Science Direct, and Google Scholar, Data were analyzed using the extraction table and presented with qualitative analysis. The initial search identified 370 articles. Seven articles were obtained after being selected through the duplication, title, abstract, and inclusion-exclusion criteria. All articles mentioned that there was no significant difference between the use of normal saline added with heparin with normal saline on arterial line patency. Based on the study, it can be concluded that the use of normal saline alone as an arterial line flush is recommended because it reduces the risk of Heparin-Induced Thrombocytopenia, allergy to heparin, bleeding and is economically more cost-saving. Abstrak: Pemantauan hemodinamik pada pasien kritis seringkali dilakukan secara invasif, menggunakan jalur arteri. Keakuratan pemantauan sangat tergantung pada patensi arterial line, yang seringkali terganggu oleh penyumbatan arteri. Sejauh ini, heparin dalam salin normal diyakini dapat mencegah komplikasi tersebut dibandingkan dengan pemberian normal salin saja. Penelitian ini bertujuan untuk membandingkan efektivitas flushing menggunakan normal saline ditambah heparin dengan penggunaan normal salin terhadap kepatenan arterial line. Penelitian ini merupakan literatur review. Kata kunci dikompilasi menggunakan critical care unit, heparinized saline, normal saline, dan arterial line patency yang dikombinasikan menggunakan boolean operator. Hasil-hasil penelitian dicari secara ekstensif melalui PubMed, Science Direct, dan Google Scholar, data dianalisis menggunakan tabel ekstraksi dan disajikan menggunakan analisis kualitatif. Pencarian awal berhasil mengidentifikasi 370 artikel. Tujuh artikel kemudian diperoleh setelah melalui seleksi menggunakan kriteria duplikasi, judul, abstrak, dan inklusi-eksklusi. Semua artikel menyebutkan bahwa tidak ada perbedaan yang signifikan antara penggunaan normal saline ditambah heparin dengan normal saline terhadap kepatenan arterial line. Berdasarkan penelitian dapat disimpulkan bahwa penggunaan flushing menggunakan normal salin saja direkomendasikan karena mengurangi risiko trombositopenia yang diinduksi heparin, alergi terhadap heparin, perdarahan dan dilihat dari biaya, lebih ekonomis.